Sustainability of Micro Hydro Projects in Lalitpur District, Nepal - Ranabhat, Ramesh; Paudyal, Prabesh (Journal of Advanced College of Engineering and Management, 2016)
Energy is one of the important necessities of the society and basic for sustainable development. The demand of electricity is increasing. Micro hydro power plants are one of the effective tools to provide rural household with energy in Nepal. These plants are also provided with government subsidies. Energy is produced by the water current from micro hydro stations. There are water availability changes due to the climatic changes and other non climatic changes; this has made water very scarce. There are few studies done in water availability and energy and even less in operator level. This study focuses in Lalitpur district in Bagmati zone, Nepal. There is lack of interlink study of the different water uses like irrigation, drinking water, animal husbandry water use etc which affects water availability. Integrating interdisciplinary water planning in energy development is one of the important steps to increase the sustainability of micro hydro plants. The operators working in micro hydro plants have already perceived the change in water availability. Thus it is important to plan the water resources using the operator’s local knowledge and situation to cope with increasing demand of electricity and the impacts of decreasing water resources. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, Page: 63-78